Timbers of the world - 10769 Timber Research and Development Association (Great Britain) (Bucks : High Wycombe, 1978)
V 2 South America -- v 4South East Asia -- v 5 Philippines and Japan -- v 6 Europe -- v 7 North America -- v 8 Australasia -- v 9 Central America and The Caribbean